2022
DOI: 10.1109/tits.2021.3107310
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Lateral Behavior Reasoning for Target Vehicles Considering Driver Preview Characteristic

Abstract: A timely understanding of target vehicles (TVs) lateral behavior is essential for the decision-making and control of host vehicle. Existing physical model-based methods such as motion-based method and multiple centerline-based method are generally constructed based on TV pose and longitudinal velocity, and tend to ignore TV preview driving characteristic and other useful information such as lateral velocity and yaw rate. To address these issues, a driver preview and multiple centerline model-based probabilisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 24 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Afterward, it creates another generation solution via duplication, crossover, and mutation, which minimizes the fitness value. Generally, the GA is used for attribute extraction [55,56]. The GA is also used to concurrently find various spot data.…”
Section: Multi-objective Genetic Algorithmmentioning
confidence: 99%
“…Afterward, it creates another generation solution via duplication, crossover, and mutation, which minimizes the fitness value. Generally, the GA is used for attribute extraction [55,56]. The GA is also used to concurrently find various spot data.…”
Section: Multi-objective Genetic Algorithmmentioning
confidence: 99%
“…A large number of studies have shown that lane-changing behavior of drivers will affect the surrounding vehicles and thus increase the occurrence of accidents. Experts in the field of intelligent transportation in Germany have called for more research into lane-changing safety in order to reduce traffic safety problems caused by lane changing [ 7 ]. The vast majority of studies mainly focus on how to unlock the turning lane change behavior, but in the actual process, due to the low-signal stimulation rate, there is delay, mainly manifested as the lane change after the driver turns on the turn signal [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%